JENIS-JENIS ANGGREK (Orchidaceae) DI TAMAN WISATA ALAM GUNUNG TAMPOMAS - Ridwan Gunawan (Wanamukti: Jurnal Penelitian Kehutanan, 2019)
The existence of orchid species in Gunung Tampomas Natural Tourism Park is still not widely known. The existence of orchids many endangered by both natural decay and excessive exploitation of orchids. Communities in Gunung Tampomas Natural Tourism Park had very little information about the beauty and benefits in particular, because of the lack of information regarding the species of orchids in the Gunung Tampomas Natural Tourism Park. The object of research is inventaritation of orchid species to conservation of orchid species in Gunung Tampomas Natural Tourism Park. The method of the research used by Exploration with determination cruise lines based LMU (Land Mapping Units). The result of orchid species are 11 species of epiphytes which has been identified as many as 10 species; one species is identified only to genus and 2 species of terrestrial orchid.